Efficacy and acceptability of pharmacological, psychosocial, and brain stimulation interventions in children and adolescents with mental disorders: an umbrella review. Issue 2 (18th May 2021) - Correll, Christoph U.; Cortese, Samuele; Croatto, Giovanni; Monaco, Francesco; Krinitski, Damir; Arrondo, Gonzalo; Ostinelli, Edoardo G.; Zangani, Caroline; Fornaro, Michele; Estradé, Andrés; Fusar‐Poli, Paolo; Carvalho, Andre F.; et al.
Abstract : Top‐tier evidence on the safety/tolerability of 80 medications in children/adolescents with mental disorders has recently been reviewed in this journal. To guide clinical practice, such data must be combined with evidence on efficacy and acceptability. Besides medications, psychosocial interventions and brain stimulation techniques are treatment options for children/adolescents with mental disorders. For this umbrella review, we systematically searched network meta‐analyses (NMAs) and meta‐analyses (MAs) of randomized controlled trials (RCTs) evaluating 48 medications, 20 psychosocial interventions, and four brain stimulation techniques in children/adolescents with 52 different mental disorders or groups of mental disorders, reporting on 20 different efficacy/acceptability outcomes. Co‐primary outcomes were disease‐specific symptom reduction and all‐cause discontinuation ("acceptability"). We included 14 NMAs and 90 MAs, reporting on 15 mental disorders or groups of mental disorders. Overall, 21 medications outperformed placebo regarding the co‐primary outcomes, and three psychosocial interventions did so (while seven outperformed waiting list/no treatment). Based on the meta‐analytic evidence, the most convincing efficacy profile emerged for amphetamines, methylphenidate and, to a smaller extent, behavioral therapy in attention‐deficit/hyperactivity disorder; aripiprazole, risperidone and several psychosocial interventions in autism; risperidone and behavioral interventions in disruptive behavior disorders; several antipsychotics in schizophrenia spectrum disorders; fluoxetine, the combination of fluoxetine and cognitive behavioral therapy (CBT), and interpersonal therapy in depression; aripiprazole in mania; fluoxetine and group CBT in anxiety disorders; fluoxetine/selective serotonin reuptake inhibitors, CBT, and behavioral therapy with exposure and response prevention in obsessive‐compulsive disorder; CBT in post‐traumatic stress disorder; imipramine and alarm behavioral intervention in enuresis; behavioral therapy in encopresis; and family therapy in anorexia nervosa. Results from this umbrella review of interventions for mental disorders in children/adolescents provide evidence‐based information for clinical decision making.